Calculating the density of electronic charge for hydrogen atom and ions like atom - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
The radial wave function R(r) and the radial distribution function P(r) as a function of (r), for the Hydrogen atom was calculated for several atomic state (1s,2s,2p,3s,3p,3d) The results were compared with Hydrogen like atom(He+,Li+2,Be+3).